DMBT1 in Adipose-Derived Stem Cell-Derived Exosomes Participates in Alleviating Ferroptosis to Promote Diabetic Wound Healing - Yan Liu; Jinnan Wang; Yujiao Cai; Xiaoke Zhu; Zhanyuan Yuan; Jiahui Dai; Dehui Che; Dongsheng Cao (Stem Cell Reviews and Reports, 2026)

Exosomes Derived from Adipose Stem Cells Enhance Angiogenesis in Diabetic Wound Via miR-146a-5p/JAZF1 Axis - Dehui Che; Xinjian Xiang; Juan Xie; Zenghong Chen; Qiong Bao; Dongsheng Cao (Stem Cell Reviews and Reports, 2024)
Chronic trauma in diabetes is a leading cause of disability and mortality. Exosomes show promise in tissue regeneration. This study investigates the role of exosomes derived from adipose stem cells (ADSC-Exos) in angiogenesis. MiRNA-seq analysis revealed significant changes in 47 genes in human umbilical vein endothelial cells (HUVECs) treated with ADSC-Exos, with miR-146a-5p highly expressed. MiR-146a-5p mimics enhanced the pro-angiogenic effects of ADSC-Exos, while inhibitors had the opposite effect. JAZF1 was identified as a direct downstream target of miR-146a-5p through bioinformatics, qRT-PCR, and dual luciferase assay. Overexpress of JAZF1 resulted in decreased proliferation, migration, and angiogenic capacity of HUVECs, and reduced VEGFA expression. This study proposes that ADSC-Exos regulate angiogenesis partly via the miR-146a-5p/JAZF1 axis. Graphical Abstract